STRATEGIC DESIGN OF A KNOWLEDGE TRANSFER SCHEME TO ADDRESS GENERATION X RETIREMENT AT PT MITRA ISWARA AND RORIMPANDEY INSURANCE BROKERS - Aziz Khan Uktolseja; Suhartono Suhartono; Antonius Anton Lie (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Workforce ageing increases the risk of institutional knowledge loss when senior leaders approach retirement, particularly in insurance brokerage firms that rely on experience, relationships, and professional judgement. This study aims to design and validate a Human Capital Management-based knowledge transfer scheme to address Generation X retirement at PT Mitra Iswara and Rorimpandey Insurance Brokers. It employed a qualitative two-cycle action research design. The data consisted of 234 employee records and qualitative evidence from 12 informants, including four knowledge donors, six knowledge receivers, and two HRD informants. Data were collected through in-depth interviews, participatory observation, document analysis, focus group discussions, and member checking. The data were analysed using reflective thematic analysis supported by source and method triangulation. The findings identify five critical tacit knowledge domains: relational knowledge, market judgement, terms and conditions negotiation, complex claims handling, and decision escalation. The second-tier leadership was partially ready. The study proposes the MIR Knowledge Transfer Relay model, integrating mentoring, job shadowing, relay method, case clinic, anonymised case note repository, reverse mentoring, readiness-based KPIs, and 30-60-90-day evaluation. The implication is that knowledge transfer should be institutionalised within succession planning and Human Capital Management policy.